Resilience as a Mediator Between Workplace Violence and Psychological Well-Being in Hospital Nurses - Mariano García-Izquierdo; María Isabel Soler-Sánchez; José Manuel de Haro García; María Isabel Ríos-Rísquez; Mariano Meseguer-de Pedro (Nursing Reports)
Workplace violence is a widespread issue affecting hospital nursing staff and significantly undermines their psychological well-being. Such violence originates from various sources, including users, colleagues, and supervisors. Psychological resilience has been linked to more favourable indicators of well-being. Background/Objectives: This study aimed to explore how different sources of workplace violence (users, colleagues, and supervisors) are related to psychological well-being and psychological resilience. Additionally, it examines whether resilience is statistically associated with a mediating role in the relationship between source-specific workplace violence and the psychological well-being of hospital nurses. Methods: A cross-sectional, multicentre, descriptive, and mediational study was conducted with a sample of 447 hospital nurses. Participants completed a self-administered questionnaire assessing workplace violence from users, colleagues, and supervisors, alongside measures of resilience, psychological well-being, and sociodemographic characteristics. Results: Among all reported incidents of workplace violence in the previous year, 69.2% were attributed to users, with verbal abuse (68.7%) being more prevalent than physical aggression (24.1%). Additionally, 37% of nurses reported experiencing violence from colleagues, and 25% from supervisors. Workplace violence from all three sources was significantly associated with both psychological well-being and resilience. Resilience was statistically associated with a mediating role in the relationship between workplace violence and nurses’ psychological health, suggesting a potential mechanism of influence without implying causality. Conclusions: The prevalence of workplace violence from users, colleagues, and supervisors among hospital nurses is notably high. Findings indicate that violence from any of these sources is negatively associated with psychological well-being. However, resilience mitigates this impact by reducing psychological distress, positioning it as a crucial personal resource for nurses facing such adversity. These results underscore the need for interventions aimed at developing and strengthening resilience among hospital nursing staff. Moreover, the findings can inform the design of organisational strategies to prevent violence and to promote resilience and well-being within healthcare settings.